PENGARUH PEMBERIAN EKSTRAK SELEDRI (Apium graveolens L.) TERHADAP EFEK SEDASI MENCIT (Mus musculus L.) DENGAN METODE TRACTION TEST DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Shinta Kusuma; Riyanto Hamid; Khoiron Nazip (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
Research on the use of celery extract (Apium graveolens L.) was carried out to determine its effect on the effect of sedation on mice (Mus musculus L.). The research method used is an experimental method with Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications with the Traction Test method. The Traction Test method is done to see the decrease in work / muscle power of the test animal. This study consisted of a control treatment (distilled water) and celery extract treatment with a dose of 1 mg / 10gBB; 2 mg / 10gBB; and 4 mg / 10gBB. Data were analyzed using variance calculation and Duncan Real Distance Difference Test (BJND). The results of the analysis of variance showed that the celery extract dose of 2 mg / 10gBB was the most effective dose in effecting sedation in mice. Information on the results of this study can be an alternative example of learning material and the contribution of teaching materials in learning Biology Class XI Semester II on Basic Competencies 3.10 Analyze the relationship between the structure of the compiler organ network in the coordination system and link it to the coordination process so that it can explain the role of nerves and hormones in the coordination mechanism and regulation and functional disturbances that may occur in human coordination systems through literature studies, observations, experiments, and simulations. Key word : Apium graveolens L., Sedation, Traction test.